The Educational Orientation of Boundary Communities at Sanggau Regency West Kalimantan - Kristianus Kristianus; Magdalena Magdalena (IJECA (International Journal of Education and Curriculum Application), 2018)
The background of this research is the condition of Indonesia-Malaysia Border Society in Entikong Sub-district and Balai essay whose life is influenced by the border atmosphere. A day they interact with Malaysians. The author wants to know how to orientation the border to education. Using qualitative and quantitative combined methods, with 3 months ' research period, the author finds the following results: (1) There is a paradox situation between hope and the reality of education shown in the border area. The findings are not adequate aspects of education, ranging from sarana-prasarana, learning facilities, preparedness, the completeness of textbooks, and so on.  (2) The orientation of community education in the frontier that successful authors find is (a) the orientation of the department, (b) Working orientation in Malaysia. (c) Orientation learning for living capital. (d) The results of this study show that most of the family's heads do not have their children who are 13-18 years old because they have to take their child to the city, while they have no family in the city to ride. (3) Education seems to evolve in the last 10 years, especially at the basic level (SD, SLTP, SLTA) because of the government's educational Assistance program.